2017
DOI: 10.21037/qims.2017.12.03
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal tract involvement in acute pancreatitis: initial findings and follow-up by magnetic resonance imaging

Abstract: Gastrointestinal tract abnormalities on MRI are common in AP and they are positively correlated with the severity of AP. It may add value for determining the severity of AP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Magnetic resonance imaging (MRI) is sensitive to the mild and edematous AP and clearly shows necrotic areas even without enhancement and assesses the inflammatory changes accurately, offering complementary information for CT in the assessment of pancreatic and peripancreatic changes. MRI has become a more and more important tool in evaluating the pancreas and peripancreas changes (11)(12)(13). Furthermore, the intravoxel incoherent motion (IVIM) MRI can help to assess the functional properties of tissues, reflecting the random microscopic motion that occurs in voxels on the MR images of water molecule (either intracellular or extracellular) and the microcirculation of blood.…”
Section: Original Articlementioning
confidence: 99%
“…Magnetic resonance imaging (MRI) is sensitive to the mild and edematous AP and clearly shows necrotic areas even without enhancement and assesses the inflammatory changes accurately, offering complementary information for CT in the assessment of pancreatic and peripancreatic changes. MRI has become a more and more important tool in evaluating the pancreas and peripancreas changes (11)(12)(13). Furthermore, the intravoxel incoherent motion (IVIM) MRI can help to assess the functional properties of tissues, reflecting the random microscopic motion that occurs in voxels on the MR images of water molecule (either intracellular or extracellular) and the microcirculation of blood.…”
Section: Original Articlementioning
confidence: 99%
“…Studies show that approximately 63% of patients with AP have gastrointestinal abnormalities (47). neoplastic lesions.…”
Section: Gastrointestinal Tract Involvementmentioning
confidence: 99%
“…The middle wall shows high signals, and the internal and external ring show hypointensity; together, these form the so-called "target sign" on T2WI, and the post-contrast scan also shows stratified enhancement (48) (Figure 13). Ji et al (47) hypothesized that the closer to the pancreas, the more serious the abnormalities in the tissues and organs; they found that the colon and duodenum were the most vulnerable organs. Gastrointestinal tract involvement plays an important role in assessing the severity and monitoring the efficacy of treatment (47).…”
Section: Gastrointestinal Tract Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…MR imaging is a noninvasive and nonionizing radiation imaging modality with high spatial resolution and excellent tissue identification through multi-parameter sequences. The broad field of view and multiplanar imaging allow MR imaging to survey the whole pelvis, which can facilitate the evaluation of lesion extension (8)(9)(10). In present pictorial review, we will exhibit DIE at different anatomic sites with surgical correlation.…”
Section: Introductionmentioning
confidence: 99%